Academic Reading Challenges in Higher Education: Identifying Barriers and Strategic Responses among EFL Students - Jusak Patty; Aldo Hattu; Inggrit O. Tanasale (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Academic reading proficiency is a fundamental determinant of success in higher education, particularly for English as a Foreign Language (EFL) students. This study examined the challenges faced by English Education Study Program students at Pattimura University when reading academic articles. Employing a mixed-methods approach with a convergent parallel design, the research integrated quantitative survey data (n=39) with qualitative insights from focus group discussions (n=8) to examine reading difficulties, contributing factors, and strategic responses. Findings revealed a hierarchical pattern of challenges, with linguistic difficulties (M=3.31) representing the most significant barrier, followed by cognitive processing (M=2.99) and strategic processing challenges (M=2.93). Complex sentence structures (M=3.28) emerged as the dominant linguistic challenge, surpassing specialized terminology (M=3.18) and unfamiliar vocabulary (M=3.21). Reader factors (M=3.11), particularly motivational sustainability with longer texts (M=3.21), exerted slightly greater influence than contextual factors (M=2.91). Students employed diverse strategies to navigate these challenges, including pre-reading orientation, vocabulary support mechanisms, and emerging technology-assisted approaches, though collaborative reading remained underutilized. Identifying